Vaccinium arboreum, Sparkleberry - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS, 2010)
FOR 258, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, and Heather V. Quintana, describes this native and small-statured tree that grows best on sandy and dry soils throughout the southeastern United States, from Virginia south to Florida, west to Texas, and north to Kansas — scientific and common names, description, allergen, storm tolerance, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.